The strategy of Sanan village tourism aware group in development of creative tourism village based on gastronomy and culture - Dewi Hermin Sutanto; Estikowati Estikowati; Fitria Earlike Anwar Sani (Jurnal Pariwisata Pesona, 2022)
The Malang City Government has made efforts to develop tourist areas through the creation of tourist villages. This is done to empower the existing potential, including the empowerment of human resources and local culture. Kampung Sanan is a very popular tourist village as a creative village based on gastronomy and culture so that it can raise the potential of the village area as an economic and cultural center. It takes the involvement of tourism-aware groups in order to develop a sustainable tourist area of Kampung Sanan. A qualitative approach was used in this study to obtain actual information in order to provide an overview of the research. From the results of the study, it was found that two strategies were prioritized in empowering the Sanan village community to become a gastronomic and cultural-based Creative Tourism Village, namely: (1) coaching the residents of Sanan Village to join a tourism awareness group; and (2) assistance in making gastronomic tour packages and cultural development through the art of Bantengan Macan Kumbang to attract tourists.